Delay in Regular Visits of Chronic Disease Patients and Its Associated Factors during the COVID-19 Pandemic - Hassan Joulaei; Zohre Foroozanfar; Arash Ziaee; Dariush Hooshyar; Mohammadjavad Loolia; Fatemeh Azadian; Maryam Fatemi (Iranian Journal of Medical Sciences, 2023)
Background: Chronic patients need regular follow-ups. During the COVID-19 pandemic, these regular visits can be affected. The delay of chronic patients and its contributing factors in their periodic visits during the COVID-19 pandemic are examined here.Methods: This cross-sectional study was conducted between February and June 2021, in Fars, Iran. Two hundred and eighty-six households with at least one chronic patient were recruited. Then, several trained questioners called the studied households and asked about the studied variables. The dependent variable was the number of delays in regular visits during the COVID-19 pandemic. The results were analyzed through Poisson regression by SPSS Statistics version 22 and GraphPad Prism software version 9. A significance level of 0.05 was considered for this study.Results: Out of 286 households 113 (73.4%) fathers, 138 (70.1%) mothers, and 17 (58.6%) children in the households reported delayed referral. In fathers, referring to the health center was significantly associated with a decrease in the number of delays (P=0.033). The higher age of the householder (P=0.005), the higher number of children (P=0.043), and having a family physician (P=0.007) in the mothers' group, also the number of children in households P=0.001 in the children group were significantly associated with increasing the number of delays.Conclusion: COVID-19 pandemic not only creates direct harmful effects but also adversely affects people in danger of chronic diseases. Delays in follow-ups are taken into account as a major challenge during the COVID-19 pandemic. This issue is not limited to rural or urban residency.